2021
DOI: 10.1089/acm.2020.0524
|View full text |Cite
|
Sign up to set email alerts
|

Laser Acupuncture Improves Tear Film Stability in Patients with Dry Eye Disease: A Two-Center Randomized-Controlled Trial

Abstract: Objectives: To investigate the efficacy of laser acupuncture (LA) therapy in patients with dry eye disease (DED). Design: A two-center randomized controlled trial. Settings/Location: The Department of Ophthalmology, Chinese Medicine at the Kaohsiung Chang Gung Memorial Hospital, and the Sunming Eye Clinic in South Taiwan. Subjects: Fifty-nine participants ages 20 to 65 years were enrolled and randomly assigned to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Laser acupuncture (LA), one of the applications of low-level laser therapy (LLLT), has been used more and more recently in clinic because of its non-invasive, non-thermal, painless, and no bleeding or blood stasis characteristics, rather than traditional acupuncture to stimulate specific regions or acupoints [1,2]. The advantages of LA also include flexible adjustable exposed zones, accurate dosing of the exposure, nonspecific patterns of receptor structures, and the ability to combine the technique with any type of treatment [1].…”
Section: Introductionmentioning
confidence: 99%
“…Laser acupuncture (LA), one of the applications of low-level laser therapy (LLLT), has been used more and more recently in clinic because of its non-invasive, non-thermal, painless, and no bleeding or blood stasis characteristics, rather than traditional acupuncture to stimulate specific regions or acupoints [1,2]. The advantages of LA also include flexible adjustable exposed zones, accurate dosing of the exposure, nonspecific patterns of receptor structures, and the ability to combine the technique with any type of treatment [1].…”
Section: Introductionmentioning
confidence: 99%
“…36,37,44 Acupuncture at LI4 is also commonly used in various eye diseases. 45,46 In this study, we administered acupuncture at these two traditional acupuncture point locations in combination to evaluate the efficacy against myopia. Some reports have mentioned the use of electroacupuncture (EA) to treat myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture regulates the autoregulatory and immunological systems through expanding vascularity and augmenting neuropeptides [107]. During DED therapy, it ameliorates tear film instability via enhanced tear protein production, modulation of hormone concentrations and lacrimal gland metabolites, enhancement of acetylcholine content in the lacrimal gland, modulation of angioactive intestinal peptides, and a decrease in pro-inflammatory cytokines in the ocular surface [108,109]. Laser acupuncture is a fusion of Chinese medicine's pathway and acupoint theory with modern laser therapy techniques.…”
Section: Laser Acupuncturementioning
confidence: 99%
“…Complications of conventional acupuncture (fainting, breaking, bending, and stinging) can likewise be averted. Accordingly, it has been indicated that laser acupuncture is a helpful supplemental treatment from the standpoint of efficacy and safety in cases where eyedrops treatment is ineffective [108]. However, laser acupuncture still requires much optimization and adjustment in terms of treatment parameters and laser device design, and the mechanisms of laser acupuncture need to be further explored.…”
Section: Laser Acupuncturementioning
confidence: 99%